Ambient observations of dimers from terpene oxidation in the gas phase: Implications for new particle formation and growth. Issue 6 (31st March 2017) - Mohr, Claudia; Lopez‐Hilfiker, Felipe D.; Yli‐Juuti, Taina; Heitto, Arto; Lutz, Anna; Hallquist, Mattias; D'Ambro, Emma L.; Rissanen, Matti P.; Hao, Liqing; Schobesberger, Siegfried; Kulmala, Markku; Mauldin, Roy L.; et al.
Abstract: We present ambient observations of dimeric monoterpene oxidation products (C16–20 Hy O6–9 ) in gas and particle phases in the boreal forest in Finland in spring 2013 and 2014, detected with a chemical ionization mass spectrometer with a filter inlet for gases and aerosols employing acetate and iodide as reagent ions. These are among the first online dual‐phase observations of such dimers in the atmosphere. Estimated saturation concentrations of 10 −15 to 10 −6 µg m −3 (based on observed thermal desorptions and group‐contribution methods) and measured gas‐phase concentrations of 10 −3 to 10 −2 µg m −3 ( 10 6 –10 7 molecules cm −3 ) corroborate a gas‐phase formation mechanism. Regular new particle formation (NPF) events allowed insights into the potential role dimers may play for atmospheric NPF and growth. The observationally constrained Model for Acid‐Base chemistry in NAnoparticle Growth indicates a contribution of 5% to early stage particle growth from the 60 gaseous dimer compounds. Key Points: First online observations of dimeric monoterpene oxidation products in both gas and particle phases in the boreal forest Measured concentrations and inferred saturation vapor pressure of gaseous dimers indicate that these compounds are formed in the gas phase An observationally constrained model indicates a contribution of up to 5% to early stage particle growth from the gaseous dimer compounds Plain Language Summary: Atmospheric aerosol particles influence climate and air quality. We present new insights into how emissions of volatile organic compounds from trees are transformed in the atmosphere to contribute to the formation and growth of aerosol particles. We detected for the first time over a forest, a group of organic molecules, known to grow particles, in the gas phase at levels far higher than expected. Previous measurements had only measured them in the particles. This finding provides guidance on how models of aerosol formation and growth should describe their appearance and fate in the atmosphere.